A computer-based framework to analyze continuous and discontinuous textural works using psychoacoustics audio descriptors - Antunes, Micael; Rossetti, Danilo; Manzolli, Jonatas (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2019: Anais do XVII Simpósio Brasileiro de Computação Musical, 2019)
This paper discusses a computer-aided musical analysis methodology anchored on psychoacoustics audio descriptors. The musicological aim is to analyze compositions centered on timbre manipulations that explore sound masses and granular synthesis as their builders. Our approach utilizes two psychoacoustics models: 1) Critical Bandwidths and 2) Loudness, and two spectral features extractors: 1) Centroid and 2) Spectral Spread. A review of the literature, contextualizing the state-of-art of audio descriptors, is followed by a definition of the musicological context guiding our analysis and discussions. Further, we present results on a comparative analysis of two acousmatic pieces: Schall (1995) of Horacio Vaggione and Asperezas (2018) of Micael Antunes. As electroacoustic works, there are no scores, therefore, segmentation and the subsequent musical analysis is an important issue to be solved. Consequently, the article ends discussing the methodological implication of the computational musicology addressed here.